Comparing Outcomes for Normal Aging and Post Stroke Populations in Interactive Metronome Therapy - Slye, Annie L. (East Carolina University, 2010)
The purpose of this study was to compare post-stroke and normal aging populations' outcomes on the Interactive Metronome® and functional motor measures after completion of Interactive Metronome® protocols. Data from a previous study with healthy participants was compared with data gathered from post-stroke participants. Percentages of change from pre- to post-test measurement with the Long Form Assessment of the Interactive Metronome® and the Nine Hole Peg Test were compared. Overall, both groups showed improvement on the outcomes, with the healthy participants averaging higher percentages of change. Data analysis did not find statistically significant differences between groups on any measure, indicating that the Interactive Metronome® may equally be effective with a post-stroke population as with the healthy aging population. These results give preliminary evidence that the Interactive Metronome® may be an effective tool in stroke rehabilitation, and add to the body of evidence that incorporating Interactive Metronome® therapy into occupational therapy interventions can lead to successful outcomes.
Keywords: Occupational Therapy; Stroke--therapy; Stroke--rehabilitation; Occupational Therapy--methods; Evaluation Studies as Topic; Pre-Post Tests; Geriatric Assessment; Aging